Pengaruh Sustainable Merketing dan Religiusitas Terhadap Loyalitas Pelanggan Produk Unilever di Tengah Konflik Palestina - Puteri, Zhiva Marietha (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the influence of sustainable marketing and religiosity on customer loyalty of Unilever products in Surabaya in the context of the Palestinian conflict. The main focus of this research is to find out whether sustainable marketing strategies that include economic, social and environmental aspects are still able to maintain customer loyalty, and to what extent the level of religiosity of consumers affects their decisions in conflict conditions. The research method used was quantitative with a purposive sampling technique of 130 respondents. The results showed that all four variables, namely economic, social, and environmental sustainable marketing, as well as religiosity, have a positive influence on customer loyalty. The findings indicate that sustainable marketing strategies remain relevant and effective in maintaining customer loyalty, even in sensitive socio-political situations, with religiosity being an additional factor that helps strengthen or weaken the relationship.